Thunderstorm effect to building damages in peninsular Malaysia - Mohd Faiz, Anwar (2015)
Geographical position of Malaysia which is located at a position near the equatorial line affects the climate and weather of this country. One of the specific features of countries near the equator is thunderstorm occurrence that often occur in particular during inter monsoon. Damage to buildings due to the thunderstorm is frequently reported in the newspapers of the country. Even so there are no specific and scientific studies be carried out to identify the most recent thunderstorm right become a threat and can cause disaster. Therefore, this study was conducted to assess the strength of thunderstorm and associate it with the damage reported. Software "Geographical Information System" is used to map the strength of thunderstorm recorded for a period of time July 2013 to June 2014. The study found there is a strong relationship for damages as well as the strength of the thunderstorm which R 2 for the relationship between the two variables are equal to 0.85. From these results, it shows that the thunderstorm was a threat to the country. In this regard, further studies related to thunderstorm and also building strength to resist from the storm is critically important.